15. Solve the equation for x: 2x+b=c%0D%0A2%0D%0A%0D%0A+%0D%0A%0D%0A=%0D%0A%0D%0ACheck this process:%0D%0A%0D%0AStep 1: 2x+b−b=c−b%0D%0A2%0D%0A%0D%0A+%0D%0A%0D%0A−%0D%0A%0D%0A=%0D%0A%0D%0A−%0D%0A%0D%0AStep 2: 2x=c−b%0D%0A2%0D%0A%0D%0A=%0D%0A%0D%0A−%0D%0A%0D%0AStep 3: 2x−2=c−b−2%0D%0A2%0D%0A%0D%0A−%0D%0A2%0D%0A=%0D%0A%0D%0A−%0D%0A%0D%0A−%0D%0A2%0D%0AStep 4: x=c2−b−2%0D%0A%0D%0A=%0D%0A%0D%0A2%0D%0A−%0D%0A%0D%0A−%0D%0A2%0D%0ACheck all of the choices that are true statements.%0D%0A%0D%0A(1 point)%0D%0AResponses%0D%0A%0D%0AThere is no error in the process.%0D%0AThere is no error in the process.%0D%0A%0D%0AThe process has an error from step 1 to step 2%0D%0AThe process has an error from step 1 to step 2%0D%0A%0D%0AThe process has an error from step 2 to step 3%0D%0AThe process has an error from step 2 to step 3%0D%0A%0D%0AThe process has an error from step 3 to step 4

1 answer

To solve the equation 2x + b = c, we can follow these steps:

Step 1: Subtract b from both sides of the equation:
2x + b - b = c - b
2x = c - b

Step 2: Divide both sides of the equation by 2:
(2x)/2 = (c - b)/2
x = (c - b)/2

There is no error in the process. The statement "There is no error in the process" is true.